Sulforaphane Alters β-Naphthoflavone-Induced Changes in Activity and Expression of Drug-Metabolizing Enzymes in Rat Hepatocytes - Lněničková, Kateřina; Dymáková, Andrea; Szotáková, Barbora; Boušová, Iva (Molecules (Basel, Switzerland), 2017)
Sulforaphane (SFN), an isothiocyanate found in cruciferous vegetables, exerts many beneficial effects on human health such as antioxidant, anti-inflammatory, and anticancer effects. The effect of SFN alone on drug-metabolizing enzymes (DMEs) has been investigated in numerous in vitro and in vivo models, but little is known about the effect of SFN in combination with cytochrome P450 (CYP) inducer. The aim of our study was to evaluate the effect of SFN on the activity and gene expression of selected DMEs in primary cultures of rat hepatocytes treated or non-treated with β-naphthoflavone (BNF), the model CYP1A inducer. In our study, SFN alone did not significantly alter the activity and expression of the studied DMEs, except for the glutathione S-transferase (GSTA1) mRNA level, which was significantly enhanced. Co-treatment of hepatocytes with SFN and BNF led to a substantial increase in sulfotransferase, aldoketoreductase 1C, carbonylreductase 1 and NAD(P)H:quinone oxidoreductase 1 activity and a marked decrease in cytochrome P450 (CYP) Cyp1a1, Cyp2b and Cyp3a4 expression in comparison to the treatment with BNF alone. Sulforaphane is able to modulate the activity and/or expression of DMEs, thus shifting the balance of carcinogen metabolism toward deactivation, which could represent an important mechanism of its chemopreventive activity.
Keywords: NAD(P)H:quinone oxidoreductase 1; Inactivation, Metabolic; beta-Naphthoflavone; drug-metabolizing enzymes; mužské pohlaví; Hepatocytes; glutathione S-transferase; enzyme activity; Male; β-naphthoflavone; cytochrome P450; sulforaphane; Sulfoxides; Isothiocyanates; isothiokyanatany; metabolická inaktivace; beta-naftoflavon; potkani Wistar; messenger RNA; Animals; zvířata; Rats, Wistar; hepatocyty; sulfoxidy; gene expression; RNA, Messenger